Electoral Victory of Yuvajana Sramika Rythu Congress Party: A Review - Sridhar Ambati (Educational Administration: Theory and Practice, 2023)
Following the sudden death of his father, Jagan Mohan Reddy sought to continue his father’s legacy, especially his popular pro-poor and welfare-oriented policies. In 2011, disillusioned with the Congress party’s refusal to appoint him as Chief Minister, Jagan Mohan Reddy resigned from the Congress and launched the YSR Congress Party. Jagan contested the by-election from Kadapa, who won the Kadapa seat by a staggering margin of 545,043 votes. This overwhelming win not only solidified his position as a prominent political leader in Andhra Pradesh but also signalled a clear rejection of the Congress Party’s handling of the state after his father’s death. The 2012 by-elections became a direct contest between the ruling Congress and the newly-formed YSR Congress Party. The by-election results were a major victory for YSRCP, as the party won 15 of the 18 assembly seats and the lone parliamentary seat up for grabs. In the 2014 Andhra Pradesh Assembly elections, despite the strong anti-Congress sentiment, the YSRCP secured a notable presence in the elections, winning 67 seats in the 175-member Assembly, despite not winning a majority. In the 2019 Andhra Pradesh Legislative Assembly elections, the YSR Congress Party achieved an overwhelming victory, securing 151 out of 175 seats in the assembly. In the same election, YSRCP also performed exceptionally well in the 2019 Indian General Elections. The party secured 22 out of 25 Lok Sabha seats in Andhra Pradesh, a stunning victory that reflected widespread discontent with the ruling TDP.